1983
DOI: 10.1111/j.1476-5381.1983.tb10067.x
|View full text |Cite
|
Sign up to set email alerts
|

The inotropic effect of ouabain and its antagonism by dihydroouabain in rat isolated atria and ventricles in relation to specific binding sites

Abstract: 1 The inotropic effect of ouabain has been studied in rat ventricles and atria. 2 The concentration-effect curve of ouabain may be fitted by a model assuming the existence of two saturable components. The component with the higher sensitivity to ouabain accounted for 30% of the maximal increase in systolic tension in ventricles and for only 5 % in atria. Increase in diastolic tension was only apparent at ouabain concentrations required to observe the low sensitivity component. [3H]-ouabain binding has been exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
7
0

Year Published

1984
1984
1998
1998

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 16 publications
5
7
0
Order By: Relevance
“…They show that the biphasic model (equation 2) has a lower variance than the monophasic model (equation 1) (P < 0.01 and P < 0.05). This is consistent with previous findings (Finet et al, 1983) Figure lc shows that the experimental data for the positive inotropic effect of ouabain in presence of EIPA 20 IuM are fitted by a monophasic curve that has the same characteristics as the low affinity inotropic component computed in the absence of EIPA (ED50 equal respectively to 0.07 ± 0.02 mM and 0.06 ± 0.01 mM; P>0.1). This confirms that EIPA affected only the high affinity component.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…They show that the biphasic model (equation 2) has a lower variance than the monophasic model (equation 1) (P < 0.01 and P < 0.05). This is consistent with previous findings (Finet et al, 1983) Figure lc shows that the experimental data for the positive inotropic effect of ouabain in presence of EIPA 20 IuM are fitted by a monophasic curve that has the same characteristics as the low affinity inotropic component computed in the absence of EIPA (ED50 equal respectively to 0.07 ± 0.02 mM and 0.06 ± 0.01 mM; P>0.1). This confirms that EIPA affected only the high affinity component.…”
Section: Resultssupporting
confidence: 79%
“…been demonstrated (Noel & Godfraind, 1984). In this tissue, the dose-effect curve of ouabain shows two components related to those high and low affinity binding sites (Finet et al, 1983). The present results show that the inotropic effect resulting from the interaction of ouabain with high affinity sites is selectively inhibited by EIPA.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…In contrast Lazdunski et al (1983), who in cultured chick heart cells could also demonstrate two ouabain binding sites, suggested that the low affinity ouabain binding, which was related to the inhibition ofthe cardiac Na' -K+ -ATPase, was probably responsible for both the cardiotonic and cardiotoxic effects of this drug. Finally, an intermediate interpretation is given by Adams et al (1982) and Finet et al (1983), who postulated from experiments on rat isolated heart muscle preparations, that the high affinity and the low affinity ouabain binding sites were involved in the inotropic action of this drug: low cardiac glycoside concentrations could cause an increased mobilization of intracellular calcium and higher ouabain concentrations result in an inhibition of the Na'-K+-pump and consequent activation of the Na'-Ca2+-exchange mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Statistics -EC 50 and E max were estimated independently for each experiment by non-linear regression using the simplest model of drug-receptor interaction (Finet et al 1983). Student's t test for determining the significance of the differences between control and infected groups was performed considering the arithmetic (E max ) or geometric (EC 50 ) means.…”
Section: Methodsmentioning
confidence: 99%